INDICATIONS FOR ANGIOCARDIOGRAPHY - Jacobson, George (1954)
Angiocardiography is indicated in selected cases of heart disease in which a definite diagnosis cannot be made by ordinary methods or in which there is reasonable expectation that the information so obtained may influence the treatment of the patient. Whenever possible, angiocardiography should be done in conjunction with cardiac catheterization. The main indication for angiocardiography is cyanotic congenital heart disease; primarily those cases in which there is a right-to-left shunt. Angiocardiography is occasionally of value in diagnosis of other types of congenital heart disease and in acquired heart disease.